Students’ Perception toward Social Media Assisted Language Learning (SMALL) for Arabic Learning - Sari, Risna Rianti; Hasibuan, Albar Adetary (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
The aims of this research were to determine the perception of students of Arabic Language Department towards the use of social media in teaching Arabic language and determine social media often used by students to help in the process of teaching Arabic language. This study used social anthropology approach in qualitative research because this study focusses on student?s perceptions towads mobile as their assistant for learning Arabic. The subject of study are 32 Arabic language education students at the State Islamic University Maulana Malik Ibrahim Malang. The results of the study show that social media can be used as a tool for language learning Arabic, can improve students' skills, and help them better interact with lecturers and classmates.